2020
DOI: 10.1002/fsn3.1467
|View full text |Cite
|
Sign up to set email alerts
|

Distinct variation in taste quality of Congou black tea during a single spring season

Abstract: The quality of Congou black tea fluctuates greatly with the changing seasons.However, variations in the taste quality of Congou black tea manufactured during a single spring season are far from clear. Here, we analyzed the taste quality of HuangJinCha (HJC) Congou black tea using sensory evaluation and found the taste quality of black tea manufactured in the early spring was better than that manufactured in the late spring. Principal component analysis (PCA) and cluster analysis for the data from the electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…The levels of amino acids exert a significant sensory effect on fresh and sweet taste of tea products. Yu et al [ 43 ] also reported that the free amino acid content was positively correlated with the tea grade, consistent with our results.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The levels of amino acids exert a significant sensory effect on fresh and sweet taste of tea products. Yu et al [ 43 ] also reported that the free amino acid content was positively correlated with the tea grade, consistent with our results.…”
Section: Resultssupporting
confidence: 93%
“…TPs exert various effects on health including anticancer activity and preventive effects on diabetes and cardiovascular diseases [ 44 ], and they are important components that affect the formation of a sweet aftertaste, thick, strong, refreshing, and bitter tastes of tea infusions [ 43 ]. Figure 3 a shows that SG contained the highest TP content (13.58%), which was approximately twice that in 3G (8.06%).…”
Section: Resultsmentioning
confidence: 99%
“…Free amino acids were detected using a e2695 Waters HPLC system (Waters, Milford, MA, USA) with the AccQ-Fluor Reagent Kit (Waters, catalog # WAT052880) according to the manufacturer’s specifications [ 6 ]. A Waters AccQ-Tag reversed-phase HPLC column (150 mm × 3.9 mm, 5 μm) was used at a flow rate of 1.0 mL·min −1 .…”
Section: Methodsmentioning
confidence: 99%
“…In market, the consuming tea categories were mainly composed of the green tea, black tea, white tea, dark tea, yellow tea and oolong tea according to the tea processing method. Among them, the consumption of green tea is the second largest tea category after black tea that reaches 8.8 × 10 5 tons per year (http://www.statista.com, accessed on 19 April 2021) [5,6]. Compared with other tea categories, green tea is rich in theanine, thus the content of theanine in green tea has gained more concern.…”
Section: Introductionmentioning
confidence: 99%
“…Non‐galloylated catechins mainly include catechin (C), gallocatechin (GC), epicatechin (EC) and epigallocatechin (EGC), whereas galloylated catechins mainly include epicatechin gallate (ECG), epigallocatechin gallate (EGCG), catechin gallate (CG) and gallocatechin gallate (GCG, Figure S1a) (Gadkari & Balaraman, 2015). Many studies have validated the contributions of catechins to tea taste and function (Liang et al ., 2016; Yu et al ., 2020). Polyphenol oxidase (PPO) can catalyse the oxidation of catechins to form high‐molecular‐weight polyphenols during the processing of black tea (Yu et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%